Think the image, don't make it! On algorithmic thinking, art education, and re-coding - Nake, Frieder (2017)
In conceptual art, the idea is not only starting point and motivation for the material work, it is often considered the work itself. In algorithmic art, thinking the process of generating the image as one instance of an entire class of images becomes the decisive kernel of the creative work. This is so because the generative algorithm is the innovative component of the artist's work. We demonstrate this by critically looking at attempts to re-construct works of early computer art by the re-coding movement. Thinking images is not the same as thinking of images. For thinking images is the act of preparing precise descriptions that control the machinic materialization of images. This kind of activity is a case of algorithmic thinking which, in turn, has become an important general aspect of current society. Art education may play an important role in establishing concrete connections between open artistic and more confined technological ways of thinking when thinking pro-gresses algorithmically.